Upaya Meningkatkan Prestasi Belajar IPA melalui Pembelajaran Group Investigation di MTs Negeri 1 Bantul - Sumiasyih (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2020)
This research aims to improve students' learning achievement in science learning through investigative group activities. This is motivated by the low learning outcomes of the